Sound Insulation Properties of Sound-Reduction Louvers with Innovative Devulcanized Rubber - Tomas VILNIŠKIS; Tomas JANUŠEVIČIUS (Archives of Acoustics)
The growing amount of used tires presents many environmental challenges around the world. Therefore, new ways to reuse used tires are being sought. One of the uses of waste tires is in sound-insulating constructions. Waste tires can be shredded into granules, which can be further devulcanized to increase their porosity. These granules can then be glued to panels and used in sound-insulating structures. Acoustic louvers were investigated in this study, with the louvers’ plates covered with rubber granule panels. Sound absorption parameters of rubber granule panels were tested across frequency bands ranging from 160 Hz to 5000 Hz. The results showed the normal incidence sound absorption coefficient reached 0.87–0.96 at 3150 Hz for 12 mm rubber granule plates. Measurements were conducted in a semi-anechoic chamber. The study has shown that rubber louvers can reduce the sound pressure level by 8 dB–12 dB, depending on the composite of the rubber granule panels and the tilt angle of the louvers’ plates.